1997
DOI: 10.1063/1.120105
|View full text |Cite
|
Sign up to set email alerts
|

The elimination of surface cross-hatch from relaxed, limited-area Si1−xGex buffer layers

Abstract: The influence of lateral dimensions on the relaxation and surface topography of linearly graded Si1−xGex buffer layers has been investigated. A dramatic change in the relaxation mechanism has been observed for depositions on Si mesa pillars of lateral dimensions 10 μm and below. Misfit dislocations are able to extend unhindered and terminate at the edges of the growth zone, yielding a surface free of cross-hatch. For lateral dimensions in excess of 10 μm orthogonal misfit interactions occur and relaxation is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…In conclusion, we have demonstrated that inserting strain-balanced Si/SiGe superlattices ͑with the SiGe layers being elastically relaxed͒ inside SiGe virtual substrates provides an alternate to, for example, limited area epitaxy 19 or vicinal substrates 20 for reducing the surface roughness, by disrupting the surface crosshatch. Moreover, some filtering of the threading dislocations by those strain-balanced superlattices has also been demonstrated in transmission electron microscopy.…”
Section: Discussionmentioning
confidence: 87%
“…In conclusion, we have demonstrated that inserting strain-balanced Si/SiGe superlattices ͑with the SiGe layers being elastically relaxed͒ inside SiGe virtual substrates provides an alternate to, for example, limited area epitaxy 19 or vicinal substrates 20 for reducing the surface roughness, by disrupting the surface crosshatch. Moreover, some filtering of the threading dislocations by those strain-balanced superlattices has also been demonstrated in transmission electron microscopy.…”
Section: Discussionmentioning
confidence: 87%
“…Growth on isolated mesas allows threading dislocations propagating through the layer to reach mesa boundaries and exit the mesa surface. Similar techniques have been applied successfully to other materials systems, including GaAs on Si, 2,3 In x Ga 1Àx As on GaAs, 4,5 Si x Ge 1Àx on Si, [5][6][7][8][9] ZnSe on GaAs, 10,11 and Hg x Cd 1Àx Te on Zn x Cd 1Àx Te. 12 For these systems, a combination of annealing to set dislocations into motion and the proximity of mesa sidewalls that act as dislocation sinks has resulted in a reduction in dislocation density at the top of the mesas.…”
Section: Introductionmentioning
confidence: 91%
“…The edges of the pillars are suitable sites for the nucleation of dislocations. This reduces the amount of cross-hatch and improves wafer surface planarity [6].…”
Section: Introductionmentioning
confidence: 99%
“…This is achieved by growing such layers on top of microscopic pillars [6][7], as shown in figure 1. The edges of the pillars are suitable sites for the nucleation of dislocations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation